PENETRASI POLITIK PADA PEMBANGUNAN PLTN DI PULAU BANGKA - Hidayat, Novendra; Darmawan, Budi; Pratama S., Putra (Asosiasi Ide Bahasa Kepri, 2024)
This study is an analysis of social movement process in collective action context of Local people in Bangka Islands to resist Nuclear Power plan establishment. This study is to analyze social movement process based on collective action which becomes a penetration for lower class people to resist the plan. It is interesting since some structural factors affects social movement penetration in Bangka Belitung. This paper used Anthony Giddens perspective about collective action on social movements. The method used was study case with qualitative descriptive analytic approach. The conclusion of this research is that there is a political network of movements supporting and opposing the development of PLTN. Apart from that, there are power relations between the two movement groups. The support group consists of BATAN which is then supported by the regional government of Bangka Belitung Islands Province, and several district governments on Bangka Island. The second party is the party that opposes the plan to build a nuclear power plant, this party is led by Walhi Bangka Belitung which is supported by local NGOs, national NGOs, mass organizations and student organizations.